OUTCOMES FOLLOWING DOUBLE KNOT SUSPENSION ARTHROPLASTY FOR BASAL JOINT ARTHRITIS OF THE THUMB - Javed, Mustafa; Nazar, Tarek; Collier, Andrew M (Journal of Ayub Medical College Abbottabad, 2015)
Background: Various surgical options used in the treatment of osteoarthritis of the basal joint of the thumb that are refractory to non-surgical management. This study was conducted to provide short term functional outcomes using the mentioned technique in treating basal joint arthritis of the thumb. Methods: We treated basal joint arthritis of the thumb by trapeziumectomy and volar oblique ligament reconstruction using flexor carpi radialis tendon and suspension interposition arthroplasty using the entire tendon split along its length and tied as a double knot at the base of the thumb metacarpal. Through a questionnaire based survey, we reviewed 24 thumbs in 24 patients with basal joint arthritis of the thumb who were followed up with the hand therapist. Postal questionnaires were sent to these patients to record DASH scores and satisfaction. Results: The mean time from surgery to discharge by the hand therapist following rehabilitation was 10 weeks. The DASH score averaged 25 points at 12 weeks postoperatively. There was statistical significance (p-value=0.0001) between the DASH score compared with time spent with the hand therapist. The postoperative net difference in grip strength and pinch grip compared with non-operated had was 9 kg and 3 kg respectively and the net difference in web span was 2 cm. Conclusion: We suggest this technique of suspension arthroplasty is a safe and effective method in treating basal joint arthritis of the thumb with good short-term functional outcomes and minimal complications. Keywords: Basal Joint Arthritis, Trapeziumectomy, Volar Oblique Ligament Reconstruction, Suspension Interposition Arthroplasty, DASH